The Overtime Effect of Social Position on Dental Caries Experience in a Group of Old-Aged Danes Born in 1914 - Ulla Krustrup, DDS, MPH, PhD; Poul Holm-Pedersen, DDS, Dr Odont (Blackwell Synergy, 2008)
The purpose of this study was to analyze the life-course effects of education, occupation, and income at ages 70, 75, 80, and 85 years, respectively, on dental caries experience of 85-year-olds.